NDVI, suitability, and carrying capacity of Dieng Plateau Forests to sustain Dieng Kulon Village tourism, Central Java, Indonesia - FATMA LESTARI; INDRA NI TUA; ADONIS MUZANNI; DANESTA FEBIANTO NUGROHO; ANDRIO A. WIBOWO; TRI WARTONO; BAIDURI WIDANARKO; ASEP SAEPULLAH; ROBIANA MODJO; MIFTACHUL FARIDA; DADAN ERWANDI; DESSY DWI ARYANI; ABDUL KADIR; ANINDHITA IRSALINA WIDIATMOKO; HENDRA HENDRA; ZICO JUNI HERWANTO; MILA TEJAMAYA; RIZAL ALFIANSYAH HAMID; FATMAH FATMAH; EZSA LARASHATI GUNAWAN; DINA LUSIANA SETYOWATI; M. FAIZIR HAFIDS (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Lestari F, Tua IN, Muzanni A, Nugroho DF, Wibowo AA, Wartono T, Widanarko B, Saepullah A, Modjo R, Farida M, Erwandi D, Aryani DD, Kadir A, Widiatmoko AI, Hendra, Herwanto ZJ, Tejamaya M, Hamid RA, Fatmah, Gunawan EL, Setyowati DL, Hafids MF. 2023. NDVI, suitability, and carrying capacity of Dieng Plateau Forests to sustain Dieng Kulon Village tourism. Biodiversitas 24: 282-289. Village tourism is a form of tourism that can support the conservation of an ecosystem. On the Dieng Plateau, Dieng Kulon is one of the tourism villages located in Banjarnegara district, Central Java, Indonesia. Despite the rapid growth of tourism in Dieng and its potential environmental consequences, information on tourism carrying capacity in Dieng is still limited. Here, this study aims to measure the suitability and carrying capacity of Dieng Kulon Village. The suitability for tourism is measured based on the Normalized Difference Vegetation Index (NDVI). Equation was used to calculate the carrying capacity. According to the findings, forest areas with a size of 23.9% and high NDVI values ranging from 0.87 to 0.91 were deemed very suitable for birdwatching and hiking activities. Agricultural land made up nearly half of the village (57.1%) with high NDVI values (ranging from 0.36-0.86) was deemed ideal for sightseeing activities. In comparison to other types of land, agricultural land had the highest carrying capacity, followed by forest land. Agricultural land can support 84.8-155.2 people per day for sightseeing activities. Forest areas are suitable for hiking and birdwatching activities. At least 51.6 to 334.9 people per day are allowed for hiking activities. Birdwatching in the forest is limited to 3.1-19.9 people per day. To conclude, carrying capacity information is very important for managing village tourism in a sustainable manner.